2015
DOI: 10.1177/1468017315572037
|View full text |Cite
|
Sign up to set email alerts
|

‘If parents are punished for asking their children to feed goats’: Supervisory neglect in sub-Saharan Africa

Abstract: Summary In the United States and the United Kingdom supervisory neglect of children is premised on a construction of childhood which characterises children as essentially vulnerable and in need of constant care and protection by parents. This Western conception has been transmitted to the countries of the sub-Sahara via the Convention on the Rights of the Child. However, the socio-economic and cultural context of African countries differs significantly from those of the United Kingdom and the United States. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…The workers indicated that they could observe from the child's physical development as well as consider their clothing to identify whether she or he has been neglected. This is possible because child neglect could be in the form of nutritional neglect (Laird, 2016;Choi & Thomas, 2015) which could cause developmental delays in children. Moreover, some parents' inability to provide proper clothing for their children could be an indication of neglectful behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The workers indicated that they could observe from the child's physical development as well as consider their clothing to identify whether she or he has been neglected. This is possible because child neglect could be in the form of nutritional neglect (Laird, 2016;Choi & Thomas, 2015) which could cause developmental delays in children. Moreover, some parents' inability to provide proper clothing for their children could be an indication of neglectful behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…Neglect may go undetected for a long time if action is not taken (Maguire & Naughton, 2016;Mennen et al, 2010), and this is more so in Ghana where child welfare and protection systems are not effective enough to provide timely intervention for neglected children or children at risk of being neglected. Most cases of neglect in Ghana are overlooked by the society due to the lack of a strong child welfare system and poor economic conditions (Laird, 2016). The situation is compounded in Ghana due to the prevalence of poverty and socio-economic disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Severe physical discipline and supervisory neglect are also limited by issues related to caregivers’ reports (i.e., recall bias, social desirability bias) and measurement problems (e.g., validity and reliability of one-item measures, short period of recall, including anyone in the household as a perpetrator). In addition, these measures may be culturally inappropriate for countries with different economic conditions, and concern over assessments that may be ethno-centric to Western post-industrial countries has been raised (Laird 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concept of neglect is shaped by poverty and culture (Coope and Theobald 2006;Roche 2013;Tang 2008;Seth and Raman 2014). In sub-Saharan Africa, for example, families are not necessarily neglecting their children when they do not seek timely healthcare or provide adequate nutrition (Laird 2016a) or when they insist their children forgo schooling in favour of animal herding (Laird 2016b).…”
Section: Conceptualising Neglectmentioning
confidence: 99%